2008
DOI: 10.1002/cm.20269
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Va phosphorylated on Ser1650 is found in nuclear speckles and redistributes to nucleoli upon inhibition of transcription

Abstract: Nuclear actin and nuclear myosins have been implicated in the regulation of gene expression in vertebrate cells. Myosin V is a class of actin-based motor proteins involved in cytoplasmic vesicle transport and anchorage, spindle-pole alignment and mRNA translocation. In this study, myosin-Va, phosphorylated on a conserved serine in the tail domain (phospho-ser(1650) MVa), was localized to subnuclear compartments. A monoclonal antibody, 9E6, raised against a peptide corresponding to phosphoserine(1650) and flank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 65 publications
0
46
1
2
Order By: Relevance
“…Nevertheless, there is increasing evidence that myosins and actins are associated with transcription and other nuclear functions. For example, myosin Va (Pranchevicius et al, 2008), myosin VI (Vreugde et al, 2006), myosin XVIb (Cameron et al, 2007) and actin, in addition to NMI, are found in eukaryotic nuclei. NMI interacts with topoisomerase II (Smukste et al, 2006), and MreB, an actin-like protein, interacts with RNA polymerase in bacteria (Kruse et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is increasing evidence that myosins and actins are associated with transcription and other nuclear functions. For example, myosin Va (Pranchevicius et al, 2008), myosin VI (Vreugde et al, 2006), myosin XVIb (Cameron et al, 2007) and actin, in addition to NMI, are found in eukaryotic nuclei. NMI interacts with topoisomerase II (Smukste et al, 2006), and MreB, an actin-like protein, interacts with RNA polymerase in bacteria (Kruse et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26] In Dundr et al 27 overexpression of a nucleus-targeted, non-polymerizing actin mutant (R62D) in HeLa cells inhibited long-range (2-3 micron) movement of an array of activated U2 snRNA minigenes to Cajal bodies. Chuang et al 28 observed a similar effect on the motion of a transgenic DHFR gene in CHO cells in the presence of a nucleustargeted G13R actin mutant, also defective in polymerization.…”
Section: Major Obstacles and Recent Progressmentioning
confidence: 99%
“…Although myosin II has been described in the nucleus (Rodgers, 2005;Li and Sarna, 2009), myosin II filaments are yet to be described in the nucleus. Nuclear myosin Va is found in nuclear speckles, which are (See poster insert) sites of RNA processing in transcriptionally active cells (Pranchevicius et al, 2008). By contrast, myosin Vb interacts with actin and RNA polymerase I in nucleoli (Lindsay and McCaffrey, 2009).…”
Section: Nuclear Myosinsmentioning
confidence: 99%